Rotação por estação na educação básica: uma proposta para o ensino de botânica - CARVALHO, Mirta Cecília Pinheiro de (Universidade Federal do Pará, 2022)
This is a qualitative research, in the narrative modality, which is based on my teaching experiences with students from the 7th year of basic education, in a municipal public school in Thailand-PA, developed in the classroom, with the aim of investigating how a teaching proposal based on hybrid teaching, in the modality rotation by station, can contribute to the teaching of botany in basic education. There were 4 subjects analyzed in this research, who were chosen based on significant information regarding the research question and the outlined objectives, according to the following criteria: i) manifestations about the potential of the teaching proposal regarding the use of technology for learning of botanical concepts; ii) manifestations about the potential of the proposal for the development of student protagonism and iii) manifestations that evidence student learning about botany. As investigative instruments, I used a questionnaire to obtain information about the students' knowledge of the topic under study, I used a diary where my reflections and perceptions throughout the research were recorded, student diaries containing the learning records on the subject, semi-structured written and audio interviews and photographic records. In order to produce new understandings about the phenomenon investigated, I use Discursive Textual Analysis as a methodology for analyzing the empirical material. After a process of immersion in the empirical material, I systematized two thematic axes of analysis: i) Hybrid teaching in basic education: technologies and student protagonism; ii) Rotation by stations: enabling learning about botanical concepts. In the first analytical axis, I discuss the potential of using digital technologies in the classroom, especially the practice of hybrid teaching through rotation by station, in order to contribute to the development of student and teacher protagonism with a view to learning botany. In the second axis, I seek to highlight the students' learning about botanical groups-resulting from the rotational process and discuss, through reflection on their own practice, the teaching learning on the subject. The analyzes reveal that the inclusion of digital technologies in the classroom enabled student engagement based on stimuli to the processes of collaboration, autonomy and authorship. Furthermore, in practice, it was possible to infer about the need for change in the teaching action, especially in an adverse technological scenario that requires the assumption of the teaching protagonism, which needs to be the author of its own practice, becoming a mediator of student learning. Regarding the learning about botanical groups, the analyzes reveal an appropriation of scientific concepts that allowed students to identify the general characteristics that define such groups from an evolutionary perspective. Furthermore, when reflecting on their own practice, the teacher realizes that, when performing differentiated teaching practices, they must be attentive to seek approximation between school scientific knowledge and the reality of students, creating conditions for the social and critical use of the knowledge learned. Thus, it is possible to consider that the investigated teaching proposal can constitute an efficient practice by providing learning processes that create conditions for authorship, in addition to allowing discussions and reflections about the roles of the teacher and the student in these processes, in particular, regarding the use of digital technologies. As a result of this study for society, an book will be made available in digital format, which presents the contribution of the emerging paradigm in education, in particular the use of technology, the foundations of the hybrid teaching proposal and the path of construction of stations involving teacher planning and student activity itineraries, in order to introduce teachers and students to new ways of teaching and learning botany.